Teaching As Meditative Inquiry: A Dialogical Exploration - Kumar, Ashwani; Downey, Adrian (Journal of the Canadian Association for Curriculum Studies, 2018)
This is a conversational paper that explores an unconventional pedagogical approach—teaching as meditative inquiry—as developed by Ashwani Kumar. This pedagogical contribution is explored and expounded upon through a related research methodology called dialogical meditative inquiry (DMI). DMI emphasizes listening holistically, learning from silence, as well as having an open and vulnerable attitude to allow for a deeper engagement with self and other participants where inner thoughts and feelings may be expressed in meditative awareness. Through this dialogic approach, the authors explore the concept of meditative inquiry and the ideas of Jiddu Krishnamurti, as well as how these have informed Kumar’s professional practice as a teacher educator and scholar. Emergent themes from this dialogue include: 1) how Kumar’s concept of meditative inquiry began and developed; 2) the connection between holistic thinking and meditative inquiry; 3) differences in how “holistic” is conceptualized from Western and Eastern perspectives; 4) teacher education candidates’ perceptions of holistic education; and 5) examination of resistance toward self-inquiry and the instrumentalization of meditative approaches.